2020
DOI: 10.1177/1357633x19894111
|View full text |Cite
|
Sign up to set email alerts
|

Concordance study between regular face-to-face dental diagnosis and dental telediagnosis using fluorescence

Abstract: Background Teledentistry consultations are an effective way to increase access to care. Whether it be for a screening, referral or even an adapted treatment plan for a certain number of patients whose access to care is complicated, demonstrating the reliability of remote consultations is essential in allowing the technique to become generalised. Aim This study aimed to determine if teledentistry consultations using fluorescence are of the same quality as regular consultations in the diagnosis of caries. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…In order to ensure the same quality of diagnosis by telemedicine as in face-to-face situations, an intraoral camera using fluorescence was chosen: the Soprocare1 (Actéon Group, Mérignac, France). The study carried out by the Montpellier CHU showed a great similarity between the two techniques and validated the use of Soprocare1 in the context of a telemedicine activity [6].…”
Section: Introductionmentioning
confidence: 73%
“…In order to ensure the same quality of diagnosis by telemedicine as in face-to-face situations, an intraoral camera using fluorescence was chosen: the Soprocare1 (Actéon Group, Mérignac, France). The study carried out by the Montpellier CHU showed a great similarity between the two techniques and validated the use of Soprocare1 in the context of a telemedicine activity [6].…”
Section: Introductionmentioning
confidence: 73%
“…A teleodontologia demonstrou apresentar diagnóstico aceitável ao exame clínico na triagem de cárie dentária (STEINMEIER et al, 2020;INQUIMBERT et al, 2020;TORUL;KAHVECI;KAHVECI, 2021). Estudos realizados por Steinmeier et al(2020) e Inquimbert et al (2020) apresentaram uma porcentagem de concordância entre o diagnóstico clínicos e remotos de 73% e 95% respectivamente.…”
Section: Os Critérios De Exclusão Foramunclassified
“…A teleodontologia demonstrou apresentar diagnóstico aceitável ao exame clínico na triagem de cárie dentária (STEINMEIER et al, 2020;INQUIMBERT et al, 2020;TORUL;KAHVECI;KAHVECI, 2021). Estudos realizados por Steinmeier et al(2020) e Inquimbert et al (2020) apresentaram uma porcentagem de concordância entre o diagnóstico clínicos e remotos de 73% e 95% respectivamente. Steinmeier et al(2020) relatou que pode ser realizada uma triagem remota eficaz e válida em termos de tempo dos tecidos moles e duros orais com base apenas em varreduras intraorais em cores reais aproximadas.…”
Section: Os Critérios De Exclusão Foramunclassified
See 1 more Smart Citation
“…Nevertheless, this usual practice causes difficulties in dentistry. Indeed, using the webcam does not offer a qualitative intraoral view and thus requires the use of an intraoral camera [ 7 , 8 ]. This article describes the attendance and management of patients in a pediatric dental department, through a teledentistry protocol, during the first COVID-19 lockdown.…”
Section: Introductionmentioning
confidence: 99%